Peran Ekonomi Islam dalam Mengatasi Judi Online - Diah Amalia; Ine Azizah; Monicha Dewi Anggraeni; Naifa Nur Marischa; Salsabila Meydiawanti; Zahra Tazkia; Edi Suresman (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the role of Islamic economics in regulating online gambling which is increasingly popular among Indonesian people, even Muslims. This study uses a qualitative method with a literature study approach to analyze the impact of online gambling and offers solutions based on Islamic economic principles. The data collected in this study were analyzed by reading, reviewing, and summarizing the results of previous studies that have been conducted on the influence of learning motivation on academic achievement in economics subjects. The results of the study indicate that online gambling damages five main aspects of the maqashid sharia, namely religion, soul, mind, property, and descendants. To overcome this problem, Islamic economics offers an approach to Islamic financial literacy education, economic empowerment through Islamic microfinance institutions such as Baitul Maal wat Tamwil (BMT), and strengthening government regulations in prohibiting and supervising online gambling practices. This study recommends collaboration between the government, financial institutions, and Islamic organizations to increase public awareness, strengthen spiritual values, and create halal economic opportunities as a more productive alternative. Thus, the application of Islamic economic principles is expected to be able to create a just, prosperous, and free society from online gambling practices.